SUSTAINABLE CUSTOMER DIGITAL ENGAGEMENT STRATEGIES FOR THE TOURISM RECOVERY PERSPECTIVE - POCINHO, Margarida; VIEIRA, Nataliya G.S.; NUNES, Celso Pereira; NECHITA, Florin (Universitatea Transilvania Brasov, 2021)
The tourism sector has continued to be one of the most affected business units in 2020 in connection with a global pandemic. Numerous regions and tourist destinations, tourist hotspots and accommodations have been subjected to serious changes with a substantial economic impact. Thereby, the question arises as to whether the capacity to respond to customers' needs through functional digital engagement strategies is efficient for supporting a recovery and sustainable development of the tourism industry. This article comments on and provides a critical analysis of the recent online strategies related to content marketing applied to the tourism sector due to a global pandemic and the need to implement a different attitude towards tourism-oriented projects. The article proposes some examples of efficient policies that fit in with changes in the world tourism market.
Keywords: sustainable tourism; customer engagement; strategy; marketing trends; digital economy